Transforming Barriers Into Opportunities: Teaching Environment and Sustainability Service-Learning Courses During the 2020 COVID-19 Pandemic - Button, C.E.; Ghezzi, S.E.; Godfrey, P.; Huminski, S.E.; Minor, J.; Silka, L. (Journal of Higher Education Outreach and Engagement, 2022)
In response to the onset of the COVID-19 pandemic, many institutions of higher learning locked down their campuses and altered their ways of teaching. This article discusses changes made to courses at five highly varied public universities in New England participating in the multiyear Campuses for Environmental Stewardship (CES) program. The primary aim of the CES program is to integrate environmental service-learning (SL) into college curricula through workshops, faculty fellowships, and mentoring. We detail how teaching strategies were altered in fall 2020 to accommodate the threat of COVID-19 in the classroom. The authors transitioned significant portions of their instruction to online formats or outdoor classrooms. Specifics about the impacts of the shift to virtual teaching–learning are discussed, with particular focus on the impacts to the service-learning components of each of the courses. © 2022 by the University of Georgia
Keywords: Campus garden; Community engagement; Covid-19; Environmental sustainability; Outdoor classroom; Service-learning; dept.fac; peer-reviewed; ⛔ No DOI found